THE ROLE OF BODY LANGUAGE AND GESTURES IN LISTENING (Modern education and development, 2024)
Body language and gestures are crucial components of non-verbal communication that play a significant role in the listening process. While much focus in communication studies tends to be on speaking and verbal exchanges, the way we listen—through our physical posture, facial expressions, and hand movements—greatly enhances understanding and promotes effective interaction. This article explores the importance of body language and gestures in listening, emphasizing how these non-verbal cues support attentiveness, empathy, and engagement in conversations. By examining relevant research and real-world examples, the article highlights the multifaceted ways in which gestures and body language contribute to successful communication and the listener’s role in fostering a positive exchange.